DETERMINAN KEJADIAN TUBERKULOSIS PARU - Putri, Putu Chrisdayanti Suada; Zamli, Zamli; Nordianiwati, Nordianiwati; Mudhofar, Muhamad Nor; Sulistiyani, Sulistiyani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Tuberculosis is an environmentally-based disease that still poses a threat to public health worldwide. Based on data from the Payakumbuh City Health Office, the Tarok Health Center Working Area has the highest incidence of pulmonary TB in Payakumbuh City in 2022. The purpose of the study was to determine the determinants of the incidence of pulmonary tuberculosis. The type of research is quantitative with a case control approach. The research was conducted at the Tarok Health Center in Payakumbuh City. The population was all TB patients who lived in the Tarok Health Center working area. As for the control population, they were people who had checked their sputum at the Tarok Health Center laboratory and were declared negative for TB by the lab results. The sample amounted to 44 cases and 44 controls. The sampling technique used in this study was purposive sampling. Data analysis was done univariate and bivariate. The results showed that there was a relationship between contact history (p value: 0.017) and the incidence of pulmonary tuberculosis. It is recommended that health center staff should increase direct visits to the homes of patients with pulmonary tuberculosis to see firsthand the condition of the physical environment of the house and to find out whether there is a possibility that the patient's family is infected so that preventive measures can be taken. For this reason, recording the patient's address in the register book must be clear and complete to facilitate home visits.Keywords: Environment, Contact History, Tuberculosis.